2014
DOI: 10.1021/jp412702g
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Luminescence and Ce3+ → Tb3+ → Eu3+ Energy Transfer of Broadband-Excited and Narrow Line Red Emitting Y2SiO5:Ce3+, Tb3+, Eu3+ Phosphor

Abstract: The Ce3+ → Tb3+ → Eu3+ energy-transfer process enables Eu3+5D0 → 7F J line emission to be sensitized by the allowed Ce3+ 4f1 → 5d1 absorption transition in near-ultraviolet (NUV) and violet spectral regions. This energy-transfer strategy is applied in Y2SiO5:Ce3+, Tb3+, Eu3+ powders, leading to line-emitting red phosphors that can be excited by short-wavelength InGaN LEDs. The blue, green, and red colors can be tuned by the ratio of Ce3+/Tb3+/Eu3+. Furthermore, the energy-transfer efficiencies and correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
87
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(96 citation statements)
references
References 42 publications
6
87
0
1
Order By: Relevance
“…Yen, energy transfer rate of f-d: f-f ions pair is approximately two orders of magnitude higher than that of f-f: f-f ions pair [36]. In our previous study of Ce 3+ →Tb 3+ →Eu 3+ energy transfer in Y 2 SiO 5 system, it is found that Tb 3+ →Eu 3+ energy transfer mechanism is the exchange interaction, which requires close sensitizer-activator distance (< 10 Å) for efficient energy transfer [18]. Due to relative low Tb 3+ →Eu 3+ energy transfer rate, it is reasonable that the Tb 3+ content in Ce 3+ →Tb 3+ → Eu 3+ energy transfer should be high (> 40 %) to maximize Tb 3+ →Eu 3+ energy transfer rate, shorten the Tb 3+ -Eu 3+ distance and alleviate MMCT process.…”
Section: Energy Transfer Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Yen, energy transfer rate of f-d: f-f ions pair is approximately two orders of magnitude higher than that of f-f: f-f ions pair [36]. In our previous study of Ce 3+ →Tb 3+ →Eu 3+ energy transfer in Y 2 SiO 5 system, it is found that Tb 3+ →Eu 3+ energy transfer mechanism is the exchange interaction, which requires close sensitizer-activator distance (< 10 Å) for efficient energy transfer [18]. Due to relative low Tb 3+ →Eu 3+ energy transfer rate, it is reasonable that the Tb 3+ content in Ce 3+ →Tb 3+ → Eu 3+ energy transfer should be high (> 40 %) to maximize Tb 3+ →Eu 3+ energy transfer rate, shorten the Tb 3+ -Eu 3+ distance and alleviate MMCT process.…”
Section: Energy Transfer Studiesmentioning
confidence: 99%
“…A. Setlur, Tb 3+ could be served as a bridge to alleviate the MMCT effect between Ce 3+ and Eu 3+ [15]. Thus, Ce 3+ →Tb 3+ →Eu 3+ is a promising strategy to enhance the red emission of Eu 3+ 4f-4f red emission, which has been verified in Na 2 Y 2 B 2 O 7 : Ce 3+ , Tb 3+ , Eu 3+ [16], GdBO 3 : Ce 3+ , Tb 3+ , Eu 3+ [17] and Y 2 SiO 5 : Ce 3+ , Tb 3+ , Eu 3+ [18]. It is found that a high Tb 3+ content is required in Ce 3+ →Tb 3+ →Eu 3+ process for sensitizing Eu 3+ red emission, such as YBO 3 :…”
Section: Introductionmentioning
confidence: 98%
“…Its ground state configuration is 4f 1 , and its first excited state configuration is 5d 1 . As a sensitizer, it was proved that the Ce 3+ [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, Er 3+ , Ho 3+ , Tb 3+ and Ce 3+ ions are used for green and red light emissions and sometimes Eu 3+ is also used for red light emission [4][5][6][7] . Tm 3+ is profoundly used for blue light emission and hence a wide combination of tri-doped rare earth ions have been reported using these rare earth ions with the dopingof Yb 3+ as sensitizer in different host materials 1,[8][9][10] .…”
Section: Introductionmentioning
confidence: 99%